PENGUKURAN KINERJA DAN AKUNTABILITAS ORGANISASI PUBLIK - Wargadinata, ella (Majalah Ilmiah UNIKOM, 2019)
The relation between performance measurement and accountability is already shown empirically and conceptually in literatures and researches. In 1999, The Government of Indonesia implemented performance accountability system as a periodic government institution accountability mechanism to give their responsibility on resources management, policy implementation based on their authority. The research consist four variables, Performance Measurement Mechanism, Instrument Quality, Organization capacity and Organization Accountability. Quantitative method used as research method with regression analysis which conducted at 28 local organizations at Bandung city, covered 161 respondents. This research conducted by conceptual framework of performance measurement by Moran (2013), Instrument quality by Van Dooren et al (2010) , organization capacity from Ingraham (2003) and Accountability concept by Koppel (2005. Research result shows that organization accountability can be achieved if the performance measurement implemented correctly. Research conclusion is Performance Measurement Mechanism, Instrument Quality and Organization capacity are influence the Organization Accountability. The research recommendation is strengthening performance measurement implementation at local level through knowledge transfer and taking consideration on organization capacity to create compatible perofrmance measurement model based on characteristic organization. Key Words: Performance Measurement, Mechanism, Quality, Capacity, Accountability, Public Sector